Catalytic asymmetric synthesis of enantioenriched β-nitronitrile bearing a C-CF3 stereogenic center. Issue 36 (22nd March 2016) - Jakhar, Ajay; Kumari, Prathibha; Nazish, Mohd; Khan, Noor-ul H.; Kureshy, Rukhsana I.; Abdi, Sayed H. R.; Suresh, E.
Abstract : CF3 substituted β-nitronitriles with an all-carbon quaternary stereogenic center have been synthesized via asymmetric cyanation reaction. Abstract : CF3 substituted β-nitronitriles with an all-carbon quaternary stereogenic center have been synthesized via asymmetric cyanation reaction. In situ generated chiral Ti IV salen complexes were used as catalysts for asymmetric addition of TMSCN to nitroolefins containing a trifluoromethylated prochiral center in the β-position, to afford the corresponding β-nitronitriles in excellent yield (up to 93%) with good enantioselectivity (up to 99%). This newly developed catalytic protocol led to the efficient synthesis of useful but challenging chiral α, α′-disubstituted β-amino acids.